Krzemienie w czwartorzędowym nadkładzie pokładu węgla brunatnego w Sieniawie = Flints in quaternary overburden of the brown coal bed in Sieniawa - Bzowski, Zbigniew; Dawidowski, Andrzej; Kropornicki, Zbigniew (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the paper, geological conditions and characteristics of found flints originated from sands and boulder clay are presented. Flints are present in Quaternary overburden of the brown coal bed in Sieniawa, Poland and they consist of fine-grained authigenic quartz, hard to identify amount of amorphous chalcedon and trace amounts of goethite and possibly moganite.
Keywords: krzemienie; czwartorzęd; badania; flints; Quaternary; researches